Completion fluid viscosity enhancing and cutting agent, preparation method thereof, and completion fluid system
By introducing functional groups that can form hydrogen bonding into the adhesive lifting agent, a supramolecular harmony system is formed, which solves the problem of degradation of the adhesive lifting agent in high temperature and high mineralization environment, and achieves the long-term stable performance of the completion fluid.
Patent Information
- Application Number
- CN202311867368.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-12-29
AI Technical Summary
The adhesive-lifting agent in the existing completion fluid is prone to degradation under high temperature and high mineralization environment, resulting in a decrease in viscosity performance and the inability to stabilize the suspension of solid-phase weighting agent, resulting in instability of the completion fluid.
The functional groups that can form hydrogen bonding are introduced into the molecular structure of the adhesive cutting agent, and the supramolecular harmony system is formed through hydrogen bonding, enhancing the structural stability of the polymer in a high-temperature and high-mineralization environment.
The dynamic convergence system formed helps the polymer maintain polymer characteristics, provides additional structural strength, and effectively suspends water-insoluble weighted materials, maintaining the long-term stable performance of the completion fluid.
Smart Images

Figure CN117843888B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oil and gas resource exploration, and in particular to a completion fluid viscosity enhancing and cutting agent, a preparation method thereof, and a completion fluid system. Background Art
[0002] As development shifts to deep formations, the proportion of various deep wells and ultra-deep wells has also increased year by year, resulting in severe technical challenges for completion fluid systems, especially key viscosity-enhancing and shear-enhancing agents in the system. At present, most of the viscosity-enhancing and shear-enhancing agents used in completion fluids directly use viscosity-enhancing and shear-enhancing polymers in the drilling fluid system. Since most of the solid particles in deep well completion fluids are weighting agents, there are few slurry particles that can form a grid structure with viscosity-enhancing and shear-enhancing polymers, and polymers are very easy to degrade in high-temperature environments for a long time, resulting in a significant decrease in their viscosity-enhancing and shear-enhancing performance. It is impossible to stably suspend a large amount of solid-phase weighting agents, resulting in instability of the completion fluid. Although the introduction of soluble organic salt weighting agents into the completion fluid system can reduce the proportion of non-water-soluble weighting materials, it will also significantly increase the electrolyte content in the completion fluid. The high-concentration electrolyte environment will not only aggravate the degradation of polymers by high temperature, but the hydration of a large amount of electrolytes will also reduce the free water content in the completion fluid. To ensure the viscosity-enhancing and shear-enhancing performance, traditional drilling fluid viscosity-enhancing and shear-enhancing polymers usually have a large molecular weight. However, the free water content in deep well high-density completion fluids is low, which is not conducive to the full dissolution of high-molecular polymers. Even if the anti-degradation performance of such polymers can meet on-site requirements, it is easy to cause polymer precipitation or excessive cross-linking due to the low free water content, causing the solid phase weighting agent to settle or the system to over-thicken.
[0003] Based on the above situation, it is imperative to develop temperature-resistant and salt-resistant viscosity-enhancing and cutting agents that can meet the needs of deep well completion operations. If appropriate functional groups that can form hydrogen bonds can be introduced into the molecular structure of the viscosity-enhancing and cutting agent, the treatment agent can form a supramolecular association system by virtue of the hydrogen bonds between its functional groups after hydration in the completion fluid. Since the high-pressure environment of the deep well can significantly enhance the hydrogen bond energy, the strong association system formed thereby helps the polymer maintain its polymer properties in a high temperature and high mineralization environment, and can also provide additional structural strength, which is conducive to suspending non-water-soluble weighting materials, thereby maintaining the long-term stability of the completion fluid.
[0004] A Chinese patent application with the publication number of “CN104140791A” and the name of “A weak gel viscosity enhancing and cutting agent for drilling fluid and its preparation method” discloses a weak gel viscosity enhancing and cutting agent and its preparation method. The molecular structure of the weak gel viscosity enhancing and cutting agent prepared in the application contains sulfonic acid groups and alkyl groups to replace hydrolysis-resistant monomers such as acrylamide, thereby improving the temperature and salt and calcium resistance of the viscosity enhancing and cutting agent. The weak gel viscosity enhancing and cutting agent is a cross-linked polymer microsphere. Under high temperature, the cross-linked network is partially unfolded, the molecular chain stretches, and the surface dissolves, so that the weighting material can be suspended, meeting the requirements of suspended sand carrying performance of clay-free drilling fluids. By using the inverse emulsion polymerization method, the product has a fast dispersion and dissolution speed and a good effect. However, the viscosity enhancing and cutting agent does not have abundant hydroxyl functional groups and cannot form a dynamic association system based on hydrogen bonding to maintain structural stability.
[0005] Therefore, it is of great significance to study a method for preparing an adhesion-enhancing and cutting agent with rich hydroxyl functional groups that can help the polymer maintain its polymer properties in a high temperature and high mineralization environment. Summary of the invention
[0006] The purpose of the present invention is to solve at least one of the above-mentioned deficiencies in the prior art. For example, one of the purposes of the present invention is to provide a simple and efficient method for preparing a completion fluid viscosity enhancing and cutting agent. For another example, another purpose of the present invention is to provide a completion fluid viscosity enhancing and cutting agent that meets the operational requirements of a deep well high temperature, high density and high mineralization completion fluid system. Another purpose of the present invention is to provide a completion fluid system with good protective performance.
[0007] In order to achieve the above-mentioned object, the present invention provides a preparation method of a completion fluid viscosity enhancing and cutting agent, which may include the following steps: at room temperature, mixing an activated sodium lignin sulfonate aqueous solution with a polymerization reaction raw material, adjusting the pH value of the solution system to neutral after the two are completely mixed to obtain a first mixed solution; nitrogen-deoxygenating the first mixed solution, adding an initiator, stirring and heating to a predetermined reaction temperature, reacting for a predetermined time, and continuously reacting to obtain a reaction system; after the reaction system is subjected to two solid-liquid separations, the insolubles obtained from the two separations are combined, dried, and ground into powder to obtain a completion fluid viscosity enhancing and cutting agent; the polymerization reaction raw material may include AM and AMPS or DMA pre-dissolved in the mixture. A and AMPS deionized water, and by mass ratio, AM:AMPS:deionized water = 7.1-28.4:6.2-24.8:75-175; DMAA:AMPS:deionized water = 9.9-39.6:6.2-24.8:75-200; the step of activating the sodium lignin sulfonate aqueous solution may include: introducing deionized water pre-dissolved with sodium lignin sulfonate into the catalyst aqueous solution, ultrasonically oscillating and slowly heating to 40-55° C. to obtain the sodium lignin sulfonate aqueous solution; withdrawing the ultrasonic oscillation and irradiating the sodium lignin sulfonate aqueous solution with a xenon lamp cold light source, and removing the light after the color of the solution changes from black to dark brown to obtain the activated sodium lignin sulfonate aqueous solution.
[0008] According to one or more exemplary embodiments of an aspect of the present invention, the step of preparing the reaction system may include: adding an initiator to the first mixed liquid, stirring and heating to 50-75° C. under a N2 atmosphere, and continuing the reaction for 4-8 hours to obtain a reaction system.
[0009] According to one or more exemplary embodiments of an aspect of the present invention, the first solid-liquid separation step may include: immersing the reaction system in excess anhydrous ethanol, and extracting to obtain a first insoluble matter and a separation liquid after standing.
[0010] According to one or more exemplary embodiments of an aspect of the present invention, the second solid-liquid separation step may include: soaking the first separation liquid in an excess saturated sodium chloride solution, separating after standing to obtain a second insoluble matter and a separation liquid, then combining the first insoluble matter and the second insoluble matter and vacuum drying them, and grinding the product into powder to obtain a viscosity enhancing and cutting agent.
[0011] According to one or more exemplary embodiments of an aspect of the present invention, the vacuum drying temperature may be 50 to 80°C.
[0012] According to one or more exemplary embodiments of an aspect of the present invention, the catalyst aqueous solution may include a MIL-100 (Fe) aqueous solution.
[0013] Another aspect of the present invention provides a completion fluid viscosity improving and cutting agent, which can be obtained by the preparation method of the completion fluid viscosity improving and cutting agent described in the above exemplary embodiment.
[0014] In another aspect, the present invention provides a high-density completion fluid system, wherein the high-density completion fluid system includes the completion fluid viscosity enhancing and shearing agent described in the above exemplary embodiment.
[0015] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:
[0016] (1) The raw materials of the preparation method provided by the present invention are common, cheap and easy to obtain, and the operation cost is low.
[0017] (2) The adhesion enhancing and cutting agent provided by the present invention has appropriate functional groups that can form hydrogen bonds, and can form a supramolecular association system by virtue of the hydrogen bonds between the functional groups, which helps the polymer maintain high polymerization properties in a high temperature and high mineralization environment.
[0018] (3) The viscosity enhancing and cutting agent provided by the present invention can provide additional structural strength, which is beneficial for suspending water-insoluble weighting materials, thereby maintaining the long-term stability of the completion fluid.
[0019] (4) The preparation method provided by the present invention has simple steps, can enhance the stability of hydrogen bonds by means of the high pressure and high mineralization environment in deep wells, and can form two homologous copolymers of adhesion and cutting agents, which have a wide range of applications.
[0020] (5) The supramolecular association system in the completion fluid system provided by the present invention is not easily destroyed by a high temperature and high mineralization environment, and can ensure that it can effectively maintain the viscosity-enhancing and shearing performance in the deep well completion fluid composed of a solid phase weighting agent and a water-soluble organic salt. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The above and other objects and / or features of the present invention will become more apparent through the following description in conjunction with the accompanying drawings, in which:
[0022] Figure 1 Shows a SEM electron microscope photograph of MIL-100 (Fe) according to an exemplary embodiment of the present invention;
[0023] Figure 2 shows an XRD pattern of MIL-100(Fe) according to an exemplary embodiment of the present invention;
[0024] Figure 3 A comparison diagram of the exothermic peaks of sodium lignin sulfonate before and after activation according to an exemplary embodiment of the present invention is shown;
[0025] Figure 4A comparison diagram of laser particle size distribution of sodium lignin sulfonate before and after activation according to an exemplary embodiment of the present invention is shown;
[0026] Figure 5 A schematic diagram of the nuclear magnetic resonance hydrogen spectrum of the completion fluid viscosity enhancing and cutting agent PAAL of Example 1 is shown. DETAILED DESCRIPTION
[0027] Hereinafter, the completion fluid viscosity enhancing and cutting agent and the preparation method thereof, and the completion fluid system of the present invention will be described in detail with reference to the accompanying drawings and exemplary embodiments.
[0028] It should be noted that “first”, “second”, “third”, etc. are merely for the convenience of description and distinction and should not be understood as indicating or implying relative importance.
[0029] First Exemplary Embodiment
[0030] This exemplary embodiment provides a method for preparing a completion fluid viscosity enhancing and cutting agent.
[0031] Figure 1 Shows a SEM electron microscope photograph of MIL-100 (Fe) according to an exemplary embodiment of the present invention; Figure 2 shows an XRD pattern of MIL-100(Fe) according to an exemplary embodiment of the present invention; Figure 3 A comparison diagram of the exothermic peaks of sodium lignin sulfonate before and after activation according to an exemplary embodiment of the present invention is shown; Figure 4 The following is a comparison of the laser particle size distribution of sodium lignin sulfonate before and after activation according to an exemplary embodiment of the present invention. Figures 1 to 4 The preparation method of the completion fluid viscosity enhancing and cutting agent of this exemplary embodiment is described below.
[0032] In this exemplary embodiment, the preparation method of the completion fluid viscosity enhancing and cutting agent mainly includes the following steps:
[0033] At room temperature, the activated sodium lignin sulfonate is poured into a container and stirred and mixed with the polymerization reaction raw materials. Here, the stirring may include magnetic stirring. After the two are completely dissolved, the pH value of the solution is adjusted to neutral, for example, the pH value of the solution can be adjusted to 7 using NaOH to obtain a first mixed solution.
[0034] Under stirring conditions, the first mixed solution is deoxygenated by nitrogen for 28 to 32 minutes, such as 29 minutes, 30 minutes or 31 minutes, and an initiator is added. In terms of mass ratio, the initiator: first mixed solution can be 0.02 to 0.06:75 to 200, such as 0.027:87, 0.039:104, 0.045:157 or 0.059:189. Stir and heat to 50 to 75°C, such as 53°C, 62°C or 74°C, under N2 atmosphere. Continue the reaction for 4 to 8 hours, such as 4.4 hours, 5.7 hours or 7.6 hours, and then stop the reaction. At this time, the dark brown viscous liquid obtained is the reaction system. Here, the initiator may include ammonium persulfate.
[0035] The reaction system is immersed in excess anhydrous ethanol, and the reaction system is allowed to stand for 0.5 to 1.5 hours, such as 0.8 hours, 1.2 hours or 1.4 hours before the first solid-liquid separation. For example, a Soxhlet extractor can be used to perform the first solid-liquid separation on the reaction system to obtain the first insoluble matter and the first separated liquid. The first separated liquid is immersed in an excess of a saturated sodium chloride solution, and the reaction system is allowed to stand for 0.5 to 1.5 hours, such as 0.7 hours, 0.9 hours or 1.2 hours before the second solid-liquid separation. The second separation can also be performed using a Soxhlet extractor. The second insoluble matter and the separated liquid are obtained. The first insoluble matter and the second insoluble matter are combined and vacuum dried. For example, the combined matter can be sent to a vacuum drying oven and vacuum dried for 8 to 16 hours, such as 9 hours, 12 hours or 14 hours, at 50 to 80 degrees Celsius, such as 56 degrees Celsius, 73 degrees Celsius or 79 degrees Celsius. The dried product is ground into powder, and the amber powder product obtained is the completion fluid viscosity-enhancing and cutting agent. Here, grinding and powdering are performed until fine powder can be observed by naked eyes. Thus, the adhesion and cutting agent contains abundant hydroxyl functional groups, and the densely distributed hydroxyl groups in its molecular structure can form a dynamic association system based on hydrogen bonding through hydrogen bonding. And because high pressure and moderate mineralization can enhance the stability of hydrogen bonds, the dynamic association system formed thereby has excellent structural stability, which is beneficial for the polymer to maintain polymer properties in a high temperature and high mineralization environment, thereby exerting an adhesion and cutting effect. In addition, the above-mentioned step of preparing the adhesion and cutting agent can be carried out in a three-necked flask.
[0036] In this exemplary embodiment, the polymerization reaction raw material may include deionized water in which AM (acrylamide) and AMPS (2-acrylamido-2-methylpropanesulfonic acid) or DMAA (N,N-dimethylacrylamide) and AMPS are pre-dissolved. In terms of mass ratio, AM:AMPS:deionized water may be 7.1-28.4:6.2-24.8:75-175, for example, 8.2:7.3:79, 10.6:9.7:119, 19.7:21.2:153 or 26.3:23.6:167. Or according to the mass ratio, DMAA:AMPS:deionized water can be 9.9-39.6:6.2-24.8:75-200, for example, 10.3:7.2:78, 13.6:13.6:138, 26.7:19.7:158 or 37.4:23.9:146.
[0037] In this exemplary embodiment, the reaction system preparation step may include: adding an initiator to the first mixed solution under stirring. Stirring and heating to 50-75°C, such as 53°C, 57°C, 62°C, 69°C, 71°C or 74°C, under an N2 atmosphere. This facilitates the smooth progress of the free radical copolymerization reaction. After continuing the reaction for 4-8 hours under stirring, the reaction is stopped to generate a reaction system. Here, the reaction system is a crude reaction product of a dark brown viscous liquid. Here, the reaction under an N2 atmosphere can isolate oxygen and ensure the smooth progress of the polymerization reaction.
[0038] In this exemplary embodiment, the step of activating the sodium lignin sulfonate solution may include: adding deionized water in which sodium lignin sulfonate is pre-dissolved to deionized water in which a catalyst is dissolved at room temperature to obtain a mixed solution. Here, the ratio of sodium lignin sulfonate to deionized water may be 1.0 to 2.5:20 to 50, for example, 1.2:23, 1.8:33 or 2.3:43. After slowly heating to 43 to 47° C., for example, 41° C., 45° C. or 46° C. under ultrasonic oscillation, the ultrasonic oscillation is removed and the solution is irradiated with a xenon lamp cold light source, and the irradiation is maintained for 1.8 to 2.2 hours, for example, 1.9 hours, 2.0 hours or 2.1 hours.
[0039] like Figure 3 As shown in the figure, the exothermic peak of sodium lignin sulfonate before activation is significantly higher than that of sodium lignin sulfonate after activation. This shows that the hydrogen bonding effect of sodium lignin sulfonate after activation is significantly enhanced. Figure 4 As shown in the figure, the average particle size of sodium lignin sulfonate before activation is as high as 200-500 μm, while the average particle size of sodium lignin sulfonate after activation is greatly reduced to 400-800 nm, and the activity of sodium lignin sulfonate in the polymerization reaction is significantly enhanced. Therefore, the activation of sodium lignin sulfonate is more conducive to the polymerization reaction with vinyl monomers such as AM (DMAA) and AMPS in the process of preparing the adhesive and cutting agent.
[0040] In this exemplary embodiment, the catalyst may include a MIL-100 (Fe) type MOF. The preparation of the MIL-100 (Fe) type MOF may include the following steps: at room temperature, dissolve ferric chloride hexahydrate in deionized water and perform ultrasonic oscillation until it is completely dispersed. At the same time, terephthalic acid is added to the above deionized water under oscillation conditions, and after the terephthalic acid is completely dissolved in the above deionized water, nitric acid is added dropwise thereto, and the deionized water is continued to be ultrasonically oscillated for 28 to 32 minutes, for example, 29 minutes, 30 minutes or 31 minutes. The deionized water is transferred to a hydrothermal synthesis reactor lined with tetrafluoroethylene, and the reaction is carried out under high temperature, for example, at 160°C for 24 hours. The suspension after the reaction is taken out and centrifuged, for example, it can be centrifuged at 8000rpm for 15 minutes. The separated insoluble matter is taken out and washed with deionized water, for example, three times, and then the washed insoluble matter is dried, for example, it can be placed in a vacuum drying oven and vacuum dried at 60°C for 8 hours. The obtained brick red powder is MIL-100 (Fe) type MOF. Figure 1 As shown in , the average particle size of MIL-100(Fe) particles is only about 100 nm, which is a typical nano-scale particle with a significant multi-angular configuration. Figure 2 As shown in , the XRD pattern of MIL-100(Fe) has sharp peaks, indicating that it has good crystallinity and presents a typical crystal structure. Therefore, MIL-100(Fe) is a nano-scale microcrystalline particle with extremely high crystallinity, which should have extremely strong catalytic activity.
[0041] Based on the above analysis, the present invention uses cheap and readily available modified polyhydroxy natural macromolecules in the preparation of adhesion and cutting agents, and conducts a ternary copolymerization reaction with two common olefin monomers to obtain a copolymer adhesion and cutting agent. When the adhesion and cutting agent is dissolved in water, the densely distributed hydroxyl functional groups in its molecular structure can form a supramolecular association system through intermolecular hydrogen bonding, thereby enhancing the structural stability of the copolymer in a high temperature and high mineralization environment, thereby meeting the needs of deep well completion operations.
[0042] Second Exemplary Embodiment
[0043] This exemplary embodiment provides a completion fluid viscosity enhancing and cutting agent.
[0044] In this exemplary embodiment, the completion fluid viscosity enhancing and cutting agent is obtained by the preparation method of the completion fluid viscosity enhancing and cutting agent described in the first exemplary embodiment, and the general structural formula of the viscosity enhancing and cutting agent is:
[0045]
[0046] Third Exemplary Embodiment
[0047] The present exemplary embodiment provides a completion fluid system.
[0048] In this exemplary embodiment, the high-density completion fluid system includes the completion fluid viscosity enhancing and shearing agent of the second exemplary embodiment described above.
[0049] In order to better understand the above exemplary embodiments, the above exemplary embodiments of the present invention are further described and elaborated below in conjunction with specific examples.
[0050] Example 1
[0051] Figure 5 A schematic diagram of the nuclear magnetic resonance hydrogen spectrum of the completion fluid viscosity enhancing and cutting agent PAAL of Example 1 is shown.
[0052] In this example, the preparation method of PAAL mainly includes the following steps:
[0053] S1: Under room temperature, pour 20-50 mL of the activated sodium lignin sulfonate aqueous solution into a three-necked flask and stir it magnetically. Pour 7.1-28.4 g (0.1-0.4 mol) AM (acrylamide), such as 8.9 g, 9.6 g, 15.7 g, 21.4 g, 25.1 g or 27.4 g, and 6.21-24.84 g (0.03-0.12 mol) AMPS, such as 7.04 g, 10.65 g, 16.78 g or 23.74 g (2-acrylamide-2-methylpropanesulfonic acid) in 75-175 mL of deionized water, such as 76 ml, 82 ml, 91 ml, 131 ml or 162 ml, into the flask under stirring. After they are completely dissolved, adjust the pH of the system to neutral using NaOH to obtain a first mixed solution.
[0054] S2: Under stirring conditions, the first mixed solution is deoxygenated by nitrogen for 30 minutes, and 0.02-0.06g of initiator, for example, 0.03g, 0.04g or 0.05g, is added to the three-necked flask to obtain the first mixed solution. The mixture is stirred under N2 atmosphere and the temperature is raised to 50-75°C, for example, 53°C, 62°C or 74°C. The reaction is continued for 4-8h, for example, 4.4h, 5.7h or 7.6h before the reaction is stopped to obtain a reaction system.
[0055] S3: Take out the reaction system and soak it in excess anhydrous ethanol, let it stand for 0.5 to 1.5 hours, such as 0.8 hours, 1.2 hours or 1.4 hours, and then use a Soxhlet extractor to perform the first solid-liquid separation to obtain the first insoluble matter and the first separation liquid. The first separation liquid is soaked in an excess sodium chloride saturated solution, let it stand for 0.5 to 1.5 hours, such as 0.8 hours, 1.2 hours or 1.4 hours, and then use a Soxhlet extractor to perform the second solid-liquid separation. The insoluble matter obtained by the two separations is combined and sent to a vacuum drying oven, and vacuum dried at 50 to 80°C, such as 56°C, 73°C or 79°C for 8 to 16 hours, such as 9 hours, 12 hours or 14 hours, and ground into powder. The obtained amber powder is the purified copolymer viscosity-enhancing and cutting agent PAAL. The molecular structure of PAAL is as follows:
[0056]
[0057] In this example, if Figure 5 As shown in the figure, δ1.49 is the proton peak of -CH3; δ1.53 is the proton peak of the primary amine -NH2; δ1.98 is the proton peak of -OH in lignin; δ2.82 is the proton peak of CH in the benzene ring in lignin, δ3.19 is the proton peak of -CH2-, and δ3.49 is the proton peak of O-CH3 in lignin. The analysis results show that the test product is consistent with the target product structure, indicating that the desired final product was successfully prepared.
[0058] Example 2
[0059] In this example, the preparation method of the completion fluid viscosity enhancing agent is substantially the same as the preparation method of PAAL in the above example 1, except that in S1, DMAA replaces AM.
[0060] In this example, the molecular structure of the completion fluid viscosity enhancing agent PDAL can be:
[0061]
[0062] In summary, the molecular structures of completion fluid viscosity enhancer PAAL and PDAL are highly similar and belong to the same series. Therefore, both can be used to prepare a high-density completion fluid system and maintain the long-term stability of the completion fluid.
[0063] Example 3
[0064] In this example, based on the completion fluid viscosity enhancing and cutting agents PAAL and PDAL provided in Example 1 and Example 2, other treatment agents are optimized to form the following three groups of high-density completion fluid systems for evaluation, and the specific components and the contents of the corresponding components are as follows by mass percentage:
[0065] (1) 300 mL water, 0.3% Na2CO3, 3% completion fluid viscosity enhancer, 4% Redu200, 1% Redu2, 1% NFA-25, 1% PGCS-1, 120% WNZY organic salt, 80% superfine barite and 160% fine first-grade barite.
[0066] (2) 300 mL of water, 0.3% Na2CO3, 3% completion fluid viscosity enhancer, 0.5% VIS-B viscosity enhancer, 4% Redu200, 1% NFA-25, 1% polyol C, 120% WNZY organic salt, 80% superfine barite and 160% fine first-grade barite.
[0067] (3) 300 mL water, 0.3% Na2CO3, 4% completion fluid viscosity enhancer, 4.5% Redu200, 1% NFA-25, 1% polyol C, 120% WNZY organic salt, 120% superfine barite and 120% fine first-grade barite. The density of the completion fluid obtained by the above three formulas is 2.2 g / cm 3 .
[0068] In this example, after the three groups of high-density completion fluid systems were prepared according to the above ratio and sealed for 24 hours, the rheological and filtration performance of the three groups of high-density completion fluid systems were tested and evaluated according to the evaluation method in the national standard "GB / T 16783.1-2014 Field Test of Drilling Fluids in the Petroleum and Natural Gas Industry Part 1: Water-Based Drilling Fluids". The evaluation test was carried out under the aging condition of 180℃×16h, and the experimental results are shown in Table 1.
[0069] Table 1 Effect of self-made viscosity enhancing and cutting agent on rheological and filtration properties of completion fluid
[0070]
[0071]
[0072] As can be seen from Table 1, the three groups of high-density completion fluid systems formed based on PAAL and PDAL respectively showed good rheological properties before and after aging, and the API filtration loss before aging was only 3.2-3.6 mL. After aging at 180°C for 16 hours, the apparent and plastic viscosities of the three groups of high-density completion fluid systems only decreased slightly, and a certain dynamic shear force was still maintained. At the same time, the API filtration loss of the system after aging was only 5.2-5.6 mL. Based on the data in Table 1, the above three groups of completion fluid systems can maintain good rheological and filtration properties before and after aging, and the temperature resistance can reach 180°C.
[0073] Example 4
[0074] In this example, three groups of high-density completion fluid systems for evaluation were formed according to the completion fluid formulas provided in Example 3.
[0075] In this example, according to the evaluation method in the petroleum and natural gas industry standard "SY / T 5613-2016 Drilling fluid test method for shale physical and chemical properties", three groups of high-density completion fluid systems were tested and evaluated for shale rolling recovery rate and hydration expansion experiments. The experimental results are shown in Table 2.
[0076] Table 2 Shale rolling recovery and hydration expansion test results of completion fluid system
[0077]
[0078] As shown in Table 2, the expansion rates of the three groups of high-density completion fluid systems formed based on PAAL and PDAL after immersion in the standard core are all lower than 1.0%, while the shale rolling recovery rate is >95%, indicating that the three completion fluid systems constructed can effectively inhibit the hydration expansion and dispersion of shale.
[0079] Example 5
[0080] In this example, three groups of high-density completion fluid systems for evaluation were formed according to the completion fluid formulas provided in Example 3.
[0081] In this example, according to the evaluation method in the petroleum and natural gas industry standard "SY / T 5613-2016 Drilling fluid test method for shale physical and chemical properties", three groups of high-density completion fluid systems were subjected to static aging experiments at 180°C for 10 days, and the sedimentation stability of the completion fluid system after aging was tested. The experimental results are shown in Table 3.
[0082] Table 3 Completion fluid system sedimentation stability test results
[0083]
[0084] As shown in Table 3, after aging at 180°C for 10 days, the three high-density completion fluid systems based on PAAL and PDAL did not leak water when opened for inspection, and the glass rod test showed that they could freely reach the bottom with a sound when touching the bottom. Then the glass rod leaned against the wall by itself, and there was no precipitation at the bottom. The density after aging did not change significantly, indicating that the three high-density completion fluid systems based on PAAL and PDAL would not thicken or separate due to long-term high temperature, and the density of the upper and lower layers maintained a high degree of consistency, proving that the system has excellent long-term high temperature resistance.
[0085] Example 6
[0086] In this example, three groups of high-density completion fluid systems for evaluation were formed according to the completion fluid formula provided in Example 3.
[0087] In this example, according to the evaluation method in the petroleum and natural gas industry standard "SY / T 6540-2021 Indoor Evaluation Method for Damage to Reservoirs by Drilling and Completion Fluids", three groups of high-density completion fluid systems were evaluated for reservoir damage. The experimental results are shown in Table 4.
[0088] Table 4 Completion fluid reservoir damage test results
[0089]
[0090] It can be seen from Table 4 that the recovery rates of the cores of the three groups of high-density completion fluid systems formed based on PAAL and PDAL are all above 90%, indicating that the damage caused to the reservoir by the three groups of completion fluid systems is relatively low, and they have good reservoir protection performance.
[0091] In summary, the viscosity enhancing and cutting agent of the present invention uses a homemade MIL-100 (Fe) type MOF as a catalyst and visible light as a light source to activate the cheap and readily available industrial-grade sodium lignin sulfonate, thereby greatly enhancing its polymerization reaction activity. Using this as a raw material, AM (DMAA) and AMPS are respectively combined for a ternary copolymerization reaction, thereby preparing two viscosity enhancing and cutting agents rich in hydroxyl functional groups. The preparation method is simple to operate, the conditions are mild, the yield is high, and it is low in toxicity and environmentally friendly. When the viscosity enhancing and cutting agent is dissolved in water, it can form a supramolecular association based on the synergistic effect of hydrogen bonds by virtue of the rich hydroxyl functional groups in its molecular structure, which is beneficial for it to maintain polymer properties in a long-term high temperature and high mineralization environment. Three groups of high-density completion fluid systems were formed based on the two completion fluid viscosity enhancing and cutting agents, and their densities all reached 2.2g / cm 3 The temperature resistance can reach 180℃, and the stability of the system can be maintained after long-term static aging. It also has good shale inhibition and reservoir protection properties.
[0092] In summary, the advantages of the present invention may include at least one of the following:
[0093] (1) The raw materials of the preparation method provided by the present invention are cheap and easy to obtain, and the production cost is low.
[0094] (2) The preparation method provided by the present invention can be carried out at room temperature and has simple experimental steps. The experimental process is low-toxic and environmentally friendly, and has a high success rate.
[0095] (3) The adhesion-enhancing and cutting agent provided by the present invention has stable properties and can provide different types of adhesion-enhancing and cutting agents based on different conditions, thus having a wide range of applications.
[0096] (4) The completion fluid system provided by the present invention has good shale inhibition and reservoir protection performance.
[0097] Although the completion fluid viscosity enhancing and cutting agent and its preparation method, and the completion fluid system of the present invention have been described above in conjunction with exemplary embodiments, it should be clear to those skilled in the art that various modifications and changes may be made to the exemplary embodiments of the present invention without departing from the spirit and scope defined by the claims.
Claims
1. A method for preparing a completion fluid viscosity enhancing and cutting agent, characterized in that: The preparation method comprises the following steps: At room temperature, the activated sodium lignin sulfonate aqueous solution is mixed with the polymerization reaction raw material, and after the two are completely mixed, the pH value of the solution system is adjusted to neutral to obtain a first mixed solution; After nitrogen is passed through the first mixed solution to remove oxygen, an initiator is added, and the mixture is stirred and heated to a predetermined reaction temperature and reacted for a predetermined time to obtain a reaction system; After the reaction system is subjected to two solid-liquid separations, the insolubles obtained from the two separations are combined, dried, ground and powdered to obtain a completion fluid viscosity enhancing and cutting agent; The polymerization reaction raw material includes deionized water in which AM and AMPS or DMAA and AMPS are pre-dissolved, and the mass ratio is AM:AMPS:deionized water = 7.1-28.4:6.2-24.8:75-175; DMAA:AMPS:deionized water = 9.9-39.6:6.2-24.8:75-200; The step of activating the sodium lignin sulfonate aqueous solution comprises: introducing deionized water pre-dissolved with sodium lignin sulfonate into the catalyst aqueous solution, ultrasonically oscillating and slowly heating to 40-55° C. to obtain the sodium lignin sulfonate aqueous solution; withdrawing the ultrasonic oscillation and irradiating the sodium lignin sulfonate aqueous solution with a xenon lamp cold light source, and removing the light after the color of the solution changes from black to dark brown to obtain the activated sodium lignin sulfonate aqueous solution.
2. The method for preparing the completion fluid viscosity enhancing and cutting agent according to claim 1, characterized in that: The steps of preparing the reaction system include: adding an initiator to the first mixed solution, stirring and heating to 50-75° C. under a N2 atmosphere, and continuing the reaction for 4-8 hours to obtain a reaction system.
3. The method for preparing the completion fluid viscosity enhancing and cutting agent according to claim 1, characterized in that: The first solid-liquid separation step includes: immersing the reaction system in excess anhydrous ethanol, and extracting to obtain the first insoluble matter and separation liquid after standing.
4. The method for preparing the completion fluid viscosity enhancing and cutting agent according to claim 3, characterized in that: The second solid-liquid separation step includes: soaking the first separation liquid in an excess NaCl saturated solution, separating after standing to obtain a second insoluble matter and a separation liquid, combining the first insoluble matter and the second insoluble matter, vacuum drying, and grinding the product into powder to obtain a viscosity-enhancing and cutting agent.
5. The method for preparing the completion fluid viscosity enhancing and cutting agent according to claim 4, characterized in that: The vacuum drying temperature is 50-80°C.
6. The method for preparing the completion fluid viscosity enhancing and cutting agent according to claim 1, characterized in that: The catalyst aqueous solution includes a MIL-100 (Fe) aqueous solution.
7. A completion fluid viscosity enhancing and cutting agent, characterized in that: The viscosity-enhancing and cutting agent is obtained by the preparation method of the completion fluid viscosity-enhancing and cutting agent according to any one of claims 1 to 6.
8. A high-density completion fluid system, characterized in that: The high-density completion fluid system includes the completion fluid viscosity enhancing and shearing agent described in claim 7.
Citation Information
Patent Citations
Weak gel visco-shearing potentiator for drilling fluid and preparation method thereof
CN104140791A
Filtrate loss reducer for high-temperature-resistant oil field drilling fluid and preparation method thereof
CN104119845A
Synthetic method for drilling mud diluent
CN1050200A